Aldose reductase deficiency in mice prevents azoxymethane-induced colonic preneoplastic aberrant crypt foci formation - Tammali, Ravinder (Oxford University Press, 2009)
Aldose reductase (AR; EC 1.1.1.21), an nicotinamide adenine dinucleotide phosphate-dependent aldo–keto reductase, has been shown to be involved in oxidative stress signaling initiated by inflammatory cytokines, chemokines and growth factors. Recently, we have shown that inhibition of this enzyme prevents the growth of colon cancer cells in vitro as well as in nude mice xenografts. Herein, we investigated the mediation of AR in the formation of colonic preneoplastic aberrant crypt foci (ACF) using azoxymethane (AOM)-induced colon cancer mice model. Male BALB/c mice were administrated with AOM without or with AR inhibitor, sorbinil and at the end of the protocol, all the mice were euthanized and colons were evaluated for ACF formation. Administration of sorbinil significantly lowered the number of AOM-induced ACF. Similarly, AR-null mice administered with AOM demonstrated significant resistance to ACF formation. Furthermore, inhibition of AR or knockout of AR gene in the mice significantly prevented AOM-induced expression of inducible nitric oxide synthase and cyclooxygenase-2 proteins as well as their messenger RNA. AR inhibition or knockdown also significantly decreased the phosphorylation of protein kinase C (PKC) β2 and nuclear factor kappa binding protein as well as expression of preneoplastic marker proteins such as cyclin D1 and β-catenin in mice colons. Our results suggest that AR mediates the formation of ACF in AOM-treated mice and thereby inhibition of AR could provide an effective chemopreventive approach for the treatment of colon cancer.